Giornata del rispetto di ogni Spiritualità (Materiali di Estetica. Terza serie, 2024)
The Giornata del Rispetto di ogni Spiritualità (Day of Respect for All Spiritualities) advocates for a cultural shift towards inclusivity and dialogue amidst increasing societal tensions. Founded in Liguria, the event emphasizes the recognition of spirituality as a universal dimension of human experience, transcending religious and secular divides. Participants are encouraged to reflect on shared values, reject absolutist claims to truth, and honor the diverse ways individuals connect with the transcendent. By fostering silent meditation and collective acknowledgment of mutual spiritual depth, the initiative seeks to transcend traditional ecumenism, addressing both interfaith and intra-faith challenges while promoting a culture of respect and harmony.
Keywords: Spirituality; interfaith dialogue; eligious pluralism